Production of ceramic membranes made from porang (Amorphophallus muelleri B.) and zeolite and its utilization on jumputan wastewater treatment - Amira Siti Ramadhani; Aristya Fahrizul; D. Dionisius; Putri Ramadhania; Lia Cundari (Jurnal Teknik Kimia, 2024)
Palembang has a rich art of weaving jumputan cloth. Jumputan fabric uses naphthol as a dye which if discharged into the river will affect the water. Porang (Amorphophallus muelleri B.) and zeolite have potential as absorbents in absorbing impurities in liquid waste from jumputan cloth through its modification into membranes. The purpose of this study was to determine the formulation and effectiveness of ceramic membranes from porang tubers and zeolites in treating jumputan cloth wastewater, and to characterize the permeate results from the membrane. This research uses ceramic membrane filtration method combined with coagulation using Poly Aluminum Chloride (PAC) and quicklime. Coagulation uses two stirring methods, namely fast and slow stirring. Filtration was carried out for 125 minutes and every 25 minutes the filtrate was sampled. After the filtration process, several parameters were analyzed, namely turbidity, color, TSS, and pH. The best turbidity value reduction was shown in membrane variation 2 at 50 minutes with a decrease of 68.71 %, a decrease in color concentration was shown in membrane variation 2 at 75 minutes operating time with a decrease of 69.19%, the decrease in TSS value is shown in membrane 2 at an operating time of 125 minutes with a decrease of 81.03 %. The highest pH increase was found in membrane variation 1 at an operating time of 125 minutes with an increase of 42.67 %. The filtration process with ceramic membranes is effective in reducing turbidity, color concentration, TSS, and increasing the pH of the waste.